Customer Recognition and Mobile Geo-Targeting - Irina Baye; Philip Hanspach; Tim Reiz; Geza Sapi (Review of Industrial Organization, 2024)
Abstract We consider competing mobile marketers that complement geo-targeting with behavior-based pricing and send personalized offers to customers. Firms observe consumers' locations and can infer their (heterogeneous) responsiveness to discounts from purchase histories. The overall profit effect of behavioral targeting is driven by firms' discount factor and consumers' transport cost and can be neutral, positive, or negative. We are the first to show that the profitability of behavioral data may depend on firms' time preferences. We derive conditions for when firms prefer more rather than less behavioral targeting.
Additional information: D43;L13;L15;M37
Keywords: 330; Mobile marketing; Location targeting; Behavioral targeting; Price discrimination; Customer data